CHILDREN ON THE INTERNET: A CONSTITUTIONAL PROBLEM (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The article addresses the complex issue of protecting minors in the digital age, highlighting its constitutional implications. It examines how the Digital Services Act (DSA) has revitalized the issue of safeguarding children’s rights online and how proceedings have been initiated against some digital giants for allegedly being harmful to minors. The discussion includes the historical context of digital maturity laws, comparing the Children’s Online Privacy Protection Act (COPPA) with the European General Data Protection Regulation (GDPR). It concludes by invoking the doctrine of “constitutional precaution”, which argues that the protection of minors’ fundamental rights should be guaranteed in the design of new technologies, emphasizing the need to balance protection measures with the safeguarding of young users’ rights.
Keywords: Children protection; vulnerability; Digital Services Act; age verification systems; Constitutional Law